Psychological Readiness for Return to Sport After Shoulder Stabilization Surgery: A Review of Current Evidence and the Role of The Shoulder Instability Return to Sport After Injury (SIRSI) Scale - Pasqualini I; Hurley ET; Khan ST; Soares RW; Grobaty L; Johnson C; Lau BC; Tjong VK; Rossi LA (Open Access Journal of Sports Medicine)
Ignacio Pasqualini,1 Eoghan T Hurley,2 Shujaa T Khan,1 Rui W Soares,1 Lauren Grobaty,1 Cole Johnson,1 Brian C Lau,2 Vehniah K Tjong,3 Luciano A Rossi4 1Department of Orthopaedic Surgery, Cleveland Clinic, Cleveland, OH, USA; 2Department of Orthopedic Surgery, Division of Hand and Upper Extremity, Duke University, Durham, NC, USA; 3Division of Orthopaedic Surgery, Northwestern University, Chicago, IL, USA; 4Hospital Italiano de Buenos Aires, Buenos Aires, ArgentinaCorrespondence: Ignacio Pasqualini, Cleveland Clinic, Orthopaedic and Rheumatology Institute, 9500 Euclid Ave, A41, Cleveland, OH, 44195, USA, Tel +1 216-457-0442, Email ignacio.pasqualini@gmail.comAbstract: Shoulder instability is a common injury in athletes that often requires surgical stabilization. While RTS rates after shoulder stabilization may be around 81%, approximately 19– 52% of athletes do not return to their preinjury level of play. Psychological factors like fear of reinjury, lack of motivation, and change in priorities are key barriers to RTS after shoulder surgery. The Shoulder Instability Return to Sport after Injury (SIRSI) scale quantitatively assesses athletes’ psychological readiness to return to sport following shoulder stabilization. Higher SIRSI scores correlate with increased likelihood of returning to preinjury level of play. However, current RTS guidelines rely heavily on time-based criteria and lack consensus on assessing psychological readiness. Adopting a more comprehensive approach that incorporates physical and psychological evaluations may better determine athletes’ readiness to RTS. Incorporating the SIRSI scale into the RTS decision-making process, alongside physical evaluations, can potentially improve RTS outcomes in athletes after shoulder stabilization surgery. Further research is needed to establish standardized protocols and validate the effectiveness of interventions aimed at optimizing psychological readiness.Keywords: shoulder instability, return to sport, psychological readiness, fear of reinjury, Shoulder Instability Return to Sport after Injury scale, SIRSI